Efficient Synthesis of N-(9-Xanthyl)-4-Toluenesulfonamides Enabled by an Addition–Cyclization Cascade of Arynes - Lu, Shan-Shan; Lu, Chong-Dao (Synlett, 2013)
An efficient synthesis of N-(9-xanthyl)-4-toluenesulfonamides is described in which salicyl N-tosylimines react with silylaryl triflates in the presence of CsF. This mild process involves an addition–cyclization cascade in which arynes are generated and trapped in situ.
Keywords: N-(9-xanthyl)-4-toluenesulfonamides; salicyl N-tosylimines; arynes; addition–cyclization; cascade